Academic Hatred: Focusing on the Influence of a Supportive Classroom Climate. (April 2022) - Lee, Minyoung; Lee, Mi Kyoung; Yaung, Huk; Lee, Taerim; Lee, Sang Min
This study aimed to examine the effects of interpersonal factors (i.e., teacher and peers) on academic hatred using the hierarchical linear model analysis. The data were collected from 1, 015 senior high school students from 43 classrooms (57.3% female) in South Korea. The results showed significant effects of teachers' academic pressure, autonomy support, and peer support on academic hatred at both the individual and classroom levels. Interestingly, teachers' academic pressure showed different effects on academic hatred at the individual and classroom levels: a negative effect at the individual level and a positive one at the classroom level. At the classroom level, peer support did not significantly influence academic hatred, while at the individual level, peer support negatively affected academic hatred by interacting with teachers' autonomy support. This paper discusses the practical implications for preventing academic hatred in the classroom.